The impact of functionality-focused social media images on positive body image: an experimental study among young Chinese women - Song, Siyi; Adnan, Hamedi Mohd; Ibrahim, Muhamad Shamsul (Frontiers in Communication, 2025)
IntroductionSocial media use is often associated with negative impacts on women's body image and mental health, as idealized portrayals disseminated through digital platforms trigger upward comparisons, body dissatisfaction, and emotional distress. As an intervention strategy, functionality-focused imagery has been introduced; however, its effectiveness in reshaping body perceptions and supporting mental wellbeing remains contested, particularly within the Asian media context.MethodsThis study examined how functionality-focused visual content on social media influences body image and mental health (including body appreciation and functionality appreciation) among young Chinese women. A total of 420 female undergraduates aged 18 to 22 were exposed to five sets of images curated from Xiaohongshu: thin active, thin posed, full active, full posed, and scenery (control). ANCOVA was used to analyze the data.ResultsANCOVA results revealed that exposure to full-figured model images significantly enhanced both body and functionality appreciation compared to thin-ideal images. Functionality-focused portrayals also buffered the negative effects of thin-ideal exposure.DiscussionThis effect may partly stem from the limited critical discourse surrounding the “muscle ideal” on Chinese social media platforms. These findings highlight the importance of promoting diverse and functionality-oriented body representations through social media channels to foster positive body image and support young women's mental health in digital environments.